The Influence Of Financial Literacy, Financial Technology And Lifestyle On Student Behavior (Case Study Of Accounting Study Program Students Receiving Kip In Private Universities In Palembang City) - Rida, Rida; Hadli, Hadli; Ikraam, Ikraam (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to examine the influence of financial literacy, the use of financial technology, and lifestyle on the financial behavior of students. The study focuses on accounting students who are recipients of the Indonesia Smart Card (KIP) at private universities in Palembang. The population in this study consists of sixth- and eighth-semester accounting students, with a sample size of 155 respondents selected through purposive sampling based on specific criteria. Data collection was conducted using an online questionnaire via Google Forms. Data analysis was performed using SPSS version 25 software, employing multiple linear regression analysis to determine the influence of each independent variable on student behavior as the dependent variable. The results of the study indicate that financial literacy, financial technology, and lifestyle have a significant influence on students' financial behavior. These findings suggest that financial understanding, adaptation to financial technology, and students' lifestyles are important factors in shaping wise financial behavior among students receiving educational assistance.